“INFLUENCIA DE LAS CLASES VIRTUALES EN EL RENDIMIENTO ACADÉMICO DE LOS ESTUDIANTES DE LA UNIDAD EDUCATIVA CELESTE CARLIER FUENTES DE SAN CAMILO, AÑO 2021” - Mamonte Zambrano, David Joel (2022)
The purpose of this case study or evidence document of the complex exam is to investigate the "Influence of virtual classes on the academic performance of the students of the Celeste Carlier Fuentes de San Camilo Educational Unit, year 2021", for the structuring and development of the research involves the use of different means, methods and study techniques, this allowed information to be collected in order to reach the origin of the problem. Of virtuality can provide the necessary support to propose possible solutions to the research problem. As a fundamental platform to obtain information from the source itself, which in the case of this research are the teachers and students of the Celeste Carlier Fuentes Educational Unit. From this point, the respective conclusions and recommendations will be established that will improve the academic performance of the student. Teaching-learning process through virtual classes, from in this way, quality education is provided.